2017
DOI: 10.1039/c7cc06785b
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependent excited state relaxation of a red emitting DNA-templated silver nanocluster

Abstract: The nanosecond excited state temporal and spectral relaxation of a purified, red-emitting DNA-templated silver nanocluster (DNA-AgNC) was characterized as a function of temperature. The findings are explained by introducing a phenomenological electronic structure diagram. The reproducibility and cyclability of the average decay time opens up the possibility of using DNA-AgNCs for decay time-based nanothermometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
68
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 37 publications
(75 citation statements)
references
References 30 publications
7
68
0
Order By: Relevance
“…The corresponding drop in the quantum yield of fluorescence from primary excitation Q (Q = Q S1 ÁQ F , Q S1 is the quantum yield of emissive S 1 state formation, Q F is the quantum yield of emission from the S 1 state) was suggested to be caused by a decrease in Q S1 and Q F (see also ESI †). 18 At this point we do not know the origin of the heterogeneity in the SF/PF ratio, but immobilization in a polymer could trap DNA-AgNCs in different conformations that would yield different rate constants in Fig. 1A.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…The corresponding drop in the quantum yield of fluorescence from primary excitation Q (Q = Q S1 ÁQ F , Q S1 is the quantum yield of emissive S 1 state formation, Q F is the quantum yield of emission from the S 1 state) was suggested to be caused by a decrease in Q S1 and Q F (see also ESI †). 18 At this point we do not know the origin of the heterogeneity in the SF/PF ratio, but immobilization in a polymer could trap DNA-AgNCs in different conformations that would yield different rate constants in Fig. 1A.…”
mentioning
confidence: 96%
“…The red-emitting DNA-AgNCs used in this publication are synthesized and HPLC-purified in the same way as described previously. 18 Steady-state and time-resolved spectroscopic data can be found in the same publication. 18 We have already demonstrated that these DNA-AgNCs can undergo OADF and upconversion fluorescence (UCF) when immobilized in a poly(vinyl alcohol) (PVA) matrix.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…20 The steady-state and time-resolved photophysical properties of the red-emitting DNA-AgNC used, have been described previously by Cerretani et al (see also ESI †). 21 It is known from literature that upon exciting DNA-AgNCs, the Franck-Condon state (FC) can evolve into a microsecond-lived dark state. 15,[22][23][24][25][26] Besides dark state formation, the FC state can either relax to the ground state (S 0 ) or evolve to the emissive state (S 1 ).…”
mentioning
confidence: 99%
“…Properties of the as-prepared r-AgNCs Fig. 1a and b indicate the TEM image and the XPS spectrum of the AgNCs labeled on the cytosine-rich DNA sequence d [T 2 C 3 AC 3 AC 4 G 2 C 3 ] (r-AgNCs), 35 respectively. As illustrated, the size of the r-AgNCs is $3.7 nm, and the XPS spectrum shows typical Ag 3d 5/2 and Ag 3d 3/2 transition bands for the silver atom.…”
Section: Resultsmentioning
confidence: 99%